Does Wikipedia matter? The effect of Wikipedia on tourist choices - Marit Hinnosaar; Toomas Hinnosaar; Michael Kummer; Olga Slivko (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2017)
We document a causal influence of online user-generated information on realworld economic outcomes. In particular, we conduct a randomized field experiment to test whether additional information on Wikipedia about cities affects tourists' choices of overnight visits. Our treatment of adding information to Wikipedia increases overnight visits by 9% during the tourist season. The impact comes mostly from improving the shorter and incomplete pages in Wikipedia.
Keywords: C93; H41; L17; L82; L83; L86; 330; field experiment; user-generated content; Wikipedia; tourism industry